93 - PILATES METHOD: A STUDY ABOUT THE INFLUENCE OF EXERCISES IN WOMEN'S MUSCULAR FORCE (Fiep Bulletin - online, 2011)
The Pilates method has been widely spread in order to increase the muscular strength and other physical features. This study aims at identifying the influence of exercises in this training method on women's muscular force. The sample was made up by thirty healthy female subjects from the minimum age of twenty-five to the maximum age of sixty-eight years who were voluntarily selected among those who had joined the training program for at least six months. The subjects were divided in three groups according to their age. Considering that the center of muscular force of the method is in the abdominal muscular system, the volunteers had their abdominal muscular force assessed through a trunk partial flexion after having carried out a Pilates' class. The results obtained were rated, put in a table and statistically analyzed between groups and inside each of the groups according to Student's test t. Remarkable performance was registered inside the groups (p < 0.05) with muscular force above the average. In the analysis between groups, the results were significant only in analysis of young adults (AJO group) and third age (TID group), with p= 0.387. The Pilates' method has proven to be efficient as a form of training of muscular force, chiefly among third age women.
Keywords: Exercise and movement/method techniques; Muscular force; Analysis and development of tasks